Sex differences in psychopathy: exploring the mediating effects of self-control, sensitivity to punishment and reward, and anticipated shame and guilt - Chew, Wei Jia (Nanyang Technological University, 2022)
Psychopathy, specified by a wide range of affective, interpersonal, and behavioural traits, has consistently been found to differ between sexes, with males displaying more psychopathic traits than females. Yet, the reasons behind this discovery remain largely unexplored. In order to elucidate the link between sex and psychopathy, this study proposed several psychological variables, namely self-control, sensitivity to reward and punishment, and anticipated shame and guilt as mediators of the sex-psychopathy relationship. The aims of this study include (i) replicating findings from past research showing that sex differences in psychopathy exist and (ii) determining if self-control, sensitivity to punishment and reward, and anticipated shame and guilt mediate the relationship between sex and psychopathy. Survey results were obtained from 69 respondents, mainly comprised of undergraduates, and subjected to linear regression and mediation analyses. Results revealed that there are sex differences in psychopathy. In particular, males scored significantly higher on psychopathy as compared to females. Pertaining to the mediation analyses, self-control, sensitivity to punishment and reward, and anticipated shame did not significantly mediate the relationship between sex and psychopathy. Only anticipated guilt was found to be a significant mediator of the sex- psychopathy relationship. Overall, the findings of this study provide new insights into the mechanisms behind sex differences in psychopathy.